2021
DOI: 10.3892/etm.2021.10029
|View full text |Cite
|
Sign up to set email alerts
|

Dl‑butylphthalide inhibits rotenone‑induced oxidative stress in microglia via regulation of the Keap1/Nrf2/HO‑1 signaling pathway

Abstract: Activated microglia are a source of superoxide which often increases oxidative stress in the brain microenvironment, increase production of reactive oxygen species (ROS) and directly or indirectly lead to dopaminergic neuronal death in the substantia nigra. Thus superoxide contributes to the pathogenesis of Parkinson's disease (PD). Evidence suggests that mitochondria are the main source of ROS, which cause oxidative stress in cells. Levels of ROS are thus associated with the function of the mitochondrial comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…For example, rotenone (Rot), a mitochondria complex I inhibitor, can induce excessive ROS generation and lead to severe oxidative stress, which is a causative factor of PD [13,14]. Rot induces liquefaction necrosis and selective DA cell degeneration in the midbrain [15,16]. 1-Methyl-4phenyl-1,2,3,6-tetrafluoropyridine (MPTP) can also cause oxidative stress and is commonly used as an inducer of PD in experimental models, especially in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rotenone (Rot), a mitochondria complex I inhibitor, can induce excessive ROS generation and lead to severe oxidative stress, which is a causative factor of PD [13,14]. Rot induces liquefaction necrosis and selective DA cell degeneration in the midbrain [15,16]. 1-Methyl-4phenyl-1,2,3,6-tetrafluoropyridine (MPTP) can also cause oxidative stress and is commonly used as an inducer of PD in experimental models, especially in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 60 ] Luo et al clarified that Dl‐butylphthalide treatment substantially reduced ROS levels, elevated mitochondrial membrane potential, and mitigated oxidative stress in rotenone‐induced microglia through activating the Keap1/Nrf2/HO‐1 signaling, showing its potential in treating PD. [ 61 ] Since vincamine was previously shown to improve kidney functions and ameliorate oxidative damage in animal models of cisplatin‐induced acute kidney injury by facilitating the Nrf2/HO‐1 pathway activation, [ 37 ] we subsequently evaluated the regulation of vincamine on oxidative stress and Nrf2/HO‐1 pathway in PD mice. We confirmed that MPTP‐induced decrease in SOD activity and GSH level, increase in ROS production and MDA level, and reduction in phosphorylated Nrf2 and HO‐1 levels was abrogated by vincamine treatment, indicating vincamine‐induced alleviation on oxidative stress through activating Nrf2/HO‐1 pathway in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NBP can exert dopaminergic neuroprotection by inhibiting microglia-mediated neuroinflammation, suggesting that NBP has a good therapeutic effect on PD ( 20 ). Thus, NBP may be a new PD treatment drug ( 21 ). It is believed that more human clinical trials will be conducted to verify the safety and effectiveness of NBP in the treatment of PD in the near future.…”
Section: Discussionmentioning
confidence: 99%